A Novel Framework Based on Mixed-Integer Linear Programming to Restore a Disintegrated Power Grid after Cascading Failures - Beyza, Jesus; Yusta, Jose M.; Ruiz-Paredes, Hector F.; Garcia-Paricio, Eduardo (Revista IEEE América Latina, 2021)
Electric power systems are prone to disturbances and contingencies, which can trigger cascading failures with severe consequences for society. These undesirable events could disintegrate the electrical infrastructure in areas with disconnected elements. In this article, we propose a novel procedure to restore a collapsed power grid composed of multiple islands and isolated assets. The framework developed identifies the power lines to be closed during the electrical network recovery stages. In the latter, link overload limits and generation thresholds are taken into account. Two disintegrated networks based on the well-known IEEE 57-bus test system are built to demonstrate the performance of our proposal. In summary, this methodology provides a solution to recover the power system optimally and reliably.